ACCOUNTING AND ANALYTICAL INFORMATION FORMATION BY BUSINESS ENTITIES UNDER CONDITIONS OF SUSTAINABLE DEVELOPMENT CONCEPT REALIZATION - N. Iershova; O. Kryvytska; Yu. Kharchuk (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. According to the results of studies of scientists researches publications and  empirical studies on accounting and analytical information, the relevance of its formation in the conditions of the concept of sustainable development increases. Attention is focused on the importance of factors influencing the generation of relevant accounting and analytical information for decision-making on sustainable development of the enterprise. The factors influencing the generation of up-to-date accounting and analytical information by focus groups are highlighted.